Predikce potenciálních míst k výstavbě retenčních nádrží v krajině na základě využití reliktů zaniklých vodohospodářských staveb Certifikovaná metodika - Mazáčková, Jana (Masaryk University Press, 2021)
Title in English: Prediction of potential locations for water-retention dams in landscape based on re-utilisation of defunct relics of water-management buildings: Certified methodology This certified methodology shows the steps to be taken by contractors and builders of small water reservoirs with a special focus on preserving and archiving cultural value of historic landscape and its evolution. The methodology describes how to find and use defunct relics of historical waterdams in modern constructions (water retention dams), from identification in the landscape, through incorporation into the project documentation of the dam construction, to basic protection during the building process itself. State legislature on historic landscape is also mentioned. Re-utilisation of historic waterdams allows for their conservation for future generations and points at features of the historic dams at risk of destruction, and which need archaeological attention during the construction works (especially the historical drainage outlet). This methodology is praxis driven, as it is actively using knowledge gained through close co-operation with contractors and builders, and reflects their needs during construction.